Oxygen Saturation and Perceived Discomfort with Different Face Masks among Dental Professionals – A Cross-sectional Study - Prarthana Manoharan; Lalithambigai Gunasekaran; Girish R. Shavi; Shankar Shanmugam; Senthil Kumar Sennan (Dentistry and Medical Research)
Introduction: The protection and efficacy of face masks during the COVID-19 pandemic have been well-documented. COVID-19 is spread by respiratory droplets, and dental professionals are mandatory to wear masks for protection. Post-COVID, it is new normal to wear a face mask in day-to-day life. Objective: It was a cross-sectional study conducted among dental professionals at Vivekananda Dental College for Women. We sought to evaluate the impact of masks on health-care workers and their arterial saturation during periods of active clinical hours. Methodology: A self-constructed pretested questionnaire of 16 queries regarding the effects of prolonged use of masks, after being analyzed by the experts of our institution, was used. People who are all dentists by profession can participate in this study. All the collected information was sent for statistical analysis. Results: The result obtained shows that the majority were using surgical reusable masks, without proper maintenance and disposal, with associated discomfort and breathlessness after wearing them for 6 h a day. While comparing the individual’s oxygen saturation levels, <95 saturation was highly correlated with N95 mask wearers, using more than 6 h/day. Conclusion: Since face masks are part of the new normal world, certain strategies can be followed to reduce the discomfort by prolonged usage such as nasal breathing, taking short breaks from wearing masks in a safe environment, and maintaining proper hydration.